2019
DOI: 10.1155/2019/1907807
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T Cells in Respiratory Health and Diseases

Abstract: Respiratory diseases compromise the health of millions of people all over the world and are strongly linked to the immune dysfunction. CD4+FOXP3+ T regulatory cells, also known as Tregs, have a central role maintaining tissue homeostasis during immune responses. Their activity and clinical impact have been widely studied in different clinical conditions including autoimmune diseases, inflammatory conditions, and cancer, amongst others. Tregs express transcription factor forkhead box P3 (FOXP3), which allows re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 125 publications
(144 reference statements)
1
18
0
1
Order By: Relevance
“…However, its role in the immunopathogenesis of PRRSV-induced lung injury is unexplored. PD1/PDL1 modulation and FoxP3 + cells have been pointed out to play a dual role upon viral infections, restricting immune inflammation-induced tissue damage and encouraging lung repair during acute phase of infection (Lin et al, 2018;Singh et al, 2019), but leading to exhaustion and suppression of antiviral immune responses in the chronic infection (Arpaia et al, 2015;Schönrich and Raftery, 2019;Wang et al, 2018). Taken together, our results highlight the upregulation of CD200R1 and FoxP3 as mechanisms involved in the constraint and recovery of lung injury during acute PRRSV infection.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…However, its role in the immunopathogenesis of PRRSV-induced lung injury is unexplored. PD1/PDL1 modulation and FoxP3 + cells have been pointed out to play a dual role upon viral infections, restricting immune inflammation-induced tissue damage and encouraging lung repair during acute phase of infection (Lin et al, 2018;Singh et al, 2019), but leading to exhaustion and suppression of antiviral immune responses in the chronic infection (Arpaia et al, 2015;Schönrich and Raftery, 2019;Wang et al, 2018). Taken together, our results highlight the upregulation of CD200R1 and FoxP3 as mechanisms involved in the constraint and recovery of lung injury during acute PRRSV infection.…”
Section: Discussionsupporting
confidence: 51%
“…CD200 receptor 1 (CD200R1), expressed on myeloid cells and B cell subsets (Poderoso et al, 2019), is an inhibitory surface receptor that might deliver inhibitory signals dampening the activation of cells which express it (Vaine and Soberman, 2014). Thus, both immune markers might play an important role inhibiting the production of proinflammatory cytokines (Elmore et al, 2014;Nedumpun et al, 2018;Singh et al, 2019;Vaine and Soberman, 2014;Wang et al, 2018), lessening the exuberant lung injury observed with virulent PRRSV-1 strains. Whereas all these markers may play a key role in PRRSV virulence, there are scarce studies analysing their role in the context of the lung lesion.…”
Section: Introductionmentioning
confidence: 99%
“…Treg lymphocytes have altered tissue concentration and/or function in chronic inflammatory conditions 57 . Treg lymphocyte tissue concentration or function is reduced in lung inflammation and chronic conditions 58,59 . Tregs are a protective immune response to the microcirculation in tissue 60 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, IFN-γ and IL-2 are mainly secreted and mediated by Th1 cells, while IL-4 and IL-6 are mainly secreted and mediated by Th2 cells. The immune response of cells depends on the activation of antigen-specific CD3 + CD4 + T cells and CD3 + CD8 + T cells [ 45 , 46 ]. CD3 is a surface marker of mature T lymphocytes.…”
Section: Discussionmentioning
confidence: 99%